THE LEGAL REGIME OF POSSESSION IN ROMAN LAW - Alina-Monica AXENTE (Challenges of the Knowledge Society)
Unlike modern legal doctrine, the Romans, practitioners by definition, saw in their possession an independent legal title. According to the Roman conception, subjective rights and states of affairs are not synonymous, and possession was a state of affairs (legally protected since the time of the republic.). As a result, they never perceived possession as an attribute of property, instead considering it only an outward sign of it. Being a simple state of affairs, in the first centuries of the Roman state the possession was deprived of legal protection. In time, however, with the evolution of the procedural realm, the legal protection of possession began to be guaranteed by the interdicts of the possessor who could place the possessor in a privileged position even towards the owner. In this sense, we mention that in the case of an action in claim, the possessor had the quality of defendant, and the owner had the quality of plaintiff. As the burden of proof fell on the plaintiff, the possessive defendant could defend himself by stating only: I possess because I possess. The article aims to follow the evolutionary path of possession from a simple state of affairs to an independent legal title whose legal protection has gained a wide scope.